The Great Frieze of the Parthenon and the Organization of the Athenian Society under the Democracy of Pericles - Mavrogiannis, Theodoros (Actual Problems of Theory and History of Art, 2021)
It is strange enough that, although several attempts were made to discern the criteria upon which the representation of the Athenians on the Parthenon-Frieze is based, there is no still consensus about the structure of the composition rendering the procession in honour of Athena, whether it was an idealized, thus an exemplary depiction of the Panathenaia on 15th Hecatombeon, when the entire population of Athens would be reunited in his social components, or a historical relief issued by the celebration of the feast in a given date between 447 and 432 B.C. The problem lies in the fact that the population of the Athenian citizens was strictly organized according to institutions, going back as far as the timocratic reform of Solon in 591 B.C., which established the subdivision in four classes of citizens on the grounds of the revenues deriving from the land property. L. Beschi thought to have recognized that the composition revealed the new subdivision of Athenians in 10 territorial tribes following the Democratic revolution of Cleisthenes in 509 B.C. But the absence from the Frieze of the lower and most populous class of citizens, the thetai, who in fact acquired a major weight after the battle at Salamis in 480 B.C., creates a lot of problems. In as much, the preeminent presence of the Athenian cavalry in the Frieze may suggest that the Democracy of Pericles was not yet entered the radical way, as it is thought for the period after the abolition of the privileges of the Council of Areios Pagos in 461 B.C. put forward by Ephialtes, the mentor of Pericles. Unfortunately, we do not know all the institutional reforms introduced by Pericles after 447 B.C., whether the daily wages to be afforded by the State to the 500 bouleutai and the elected members of the tribunal of Heliaia were accompanied by a military reform of the cavalry. What seems to be true is that the Democracy of Pericles has preserved a class of aristocracy, which appears only in the Frieze, to be identified with the two upper classes of the Solonian constitution. We do not have, therefore, at our disposal any clue to ascertain that the Solonian constitution was abolished or surpassed by the new Democratic institutions. In fact, the number of the knights in the Frieze of Parthenon 144, as they are represented in units of 3 knights, should be precise, and not indicative, of the recruitment of the cavaliers through the 48 naucrariai, the ancient territorial districts for the levies of the State of Solon. It should be remembered that an outstanding position in the Frieze is reserved to the metoikoi, the strangers domiciliating in Athens who contributed to the organization of the feasts, because of their wealth. Thus, we will stress to explain the most profound structure of the Athenian society by reevaluating the iconography of the Great Frieze of Parthenon.
Keywords: Parthenon; Athens; Pericles; reliefs of the great frieze; art and society